Efficiency Analysis Of Financing in Achieving Sustainable Development Goals in East Nusa Tenggara Province - Sir, Monsar Marito; Kaluge, David; Saputra, Putu Mahardika Adi (Journal of International Conference Proceedings, 2023)
This study aims to measure the efficiency level of the regency and cities as a decision-making unit with Government Expenditures related to financing the Achievement of Sustainable Development Goals in East Nusa Tenggara Province. This study used the Data Envelopment Analysis method (DEA) with the output-oriented (VRS) using data from 22 regencies/cities. Input variables are health expenditure, education expenditure, housing and public facilities expenditure, economy expenditure, and social protection expenditure. Output variables are SDGs-1,3,4,6,8 and 9 from 2017 until 2021. The results show that from 2017 to 2021 in East Nusa Tenggara Province, Kupang City was efficient in Goals 1, 3, 4, 6, and 9 but not efficient in Goal 8 in 2021, Ngada Regency was efficient in Goals 3 and 4, and East Flores Regency was efficient in Goal 4.